The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3922/j.psns.2012.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Restricted stimulus control in stimulus control shaping with a capuchin monkey.

Abstract: Teaching the first instances of arbitrary matching to sample to nonhumans can prove difficult and time consuming. Stimulus control relations may develop that differ from those intended by the experimenter – even when stimulus control shaping procedures are used. This paper reports efforts to identify sources of shaping program failure with a capuchin monkey. Procedures began with a baseline of identity matching. During subsequent shaping trials, compound comparison stimuli had two components – one identical to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
3
0
4
Order By: Relevance
“…With minimally verbal individuals, we have observed instances in which final performance breakdowns occurred when the difference between the final and penultimate program steps differed by only a few pixels – even one – out of hundreds that comprised form stimuli to be discriminated. This phenomenon is also demonstrable with nonhuman primates doing similar tasks (Brino et al, 2011, 2012). …”
Section: The Present Challenge and Program Objectivementioning
confidence: 71%
“…With minimally verbal individuals, we have observed instances in which final performance breakdowns occurred when the difference between the final and penultimate program steps differed by only a few pixels – even one – out of hundreds that comprised form stimuli to be discriminated. This phenomenon is also demonstrable with nonhuman primates doing similar tasks (Brino et al, 2011, 2012). …”
Section: The Present Challenge and Program Objectivementioning
confidence: 71%
“…; see Alfaro, Silva, & Rylands, 2012, for an explanation of the new nomenclature for robust capuchins, formerly part of the Cebus genus). As noted, Raul had an extensive MTS history, including (1) generalized IDMTS (Galvão et al, 2005; Brino, Galvão, & Barros, 2009), (2) ARBMTS with (a) positive outcomes on tests of restricted control and (b) previous negative outcomes on symmetry tests (Brino, 2007; Brino et al, 2012), and (3) positive outcomes on tests for exclusion (Brino et al, 2010). Raul was housed in a steel wire cage measuring 2.5 m 3 half covered by Monk and Num ceramic tiles.…”
Section: Methodsmentioning
confidence: 99%
“…A small amount of prior work addressed this needed methodological development. For example, two studies showed that capuchin monkeys can acquire arbitrary stimulus-stimulus relations consistent with the development of select and reject control (c.f., Brino, Assumpção, Campos, Galvão, & McIlvane, 2010; Brino, Galvão, Barros, Goulart, & McIlvane, 2012). To date, however, no study has used the methodology to systematically assess whether necessary select or reject relations have been established within a stimulus equivalence framework with nonhumans.…”
Section: Introductionmentioning
confidence: 99%
“…No terceiro procedimento de modelagem de controle de estímulos aplicado com o sujeito Raul, neste caso envolvendo transformações graduais nos estímulos de comparação (ver Figura 1 de Brino et al, 2012), muitas sessões de treino foram necessárias para a demonstração do critério de aprendizagem em todos os passos do protocolo de treino. Além disso, diminuições bruscas de desempenho na transição entre alguns passos foram também observadas.…”
Section: ) Modelagem De Controle De Estímulosunclassified
“…Além disso, diminuições bruscas de desempenho na transição entre alguns passos foram também observadas. Para Raul, assim como ocorreu com Guga, testes de controle restrito foram aplicados para avaliar se elementos similares que se mantinham nos modelos e comparações em passos avançados do treino ainda controlavam o responder (ver Figuras 2 e 3 de Brino et al, 2012). Os resultados nesses testes indicaram que Raul respondia sob controle de relações de identidade e não de relações arbitrárias, pelo menos na maior parte dos passos da modelagem (ver Figura 5 de Brino et al, 2012).…”
Section: ) Modelagem De Controle De Estímulosunclassified